Difficulties in retail planning: The general plan of retail in Castilla y Léon (Ciudades, 2018)
The retail network in Castilla y León has a clear correspondence with the regional urban system, with its weakness and its singularities. The development of new big retail structures and malls, clearly underdeveloped comparing with other Spanish Regions, increases the territorial dependence on main urban centres and also impacts in the traditional retail network with strength. The rural areas and the historical neighbourhoods or centres run the risk of losing their vitality. The retail planning, managed by the Regional administration, tries to balance new and traditional trade structures, however the commerce laws impose in Spain a specific authorization for commercial centres, malls and other “big formats”. But the policy is oriented in every case by the decision making process, in a conflictive context between different commercial interests. In this context we detect a misunderstanding of the urban and environmental impacts.
Keywords: regional planning; urban retail; commerce management